The Effect of Capital Intensity, Liquidity, and Firm Size on Tax Aggressiveness In Property and Real Estate Sub Sector Companies Listed In The Indonesian Stock Exchange 2017-2021 Period - Juwita*, Ratih; Antoni, Antoni; Usman, Susanti (Universitas Syiah Kuala, 2023)
This study aims to analyze the effect of capital intensity, liquidity, and company size on tax aggressiveness.The population in this study are property and real estate sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The sampling method was purposive sampling and obtained a sample of 15 companies. The analytical technique used in this research is multiple linear regression analysis. The data was processed using SPSS. The results of this study indicate that the size of the company has an effect on tax aggressiveness, while capital intensity and liquidity have no effect on tax aggressiveness. Then capital intensity, liquidity and firm size simultaneously affect tax aggressiveness.